Optimalisasi Supervisi Keperawatan di Ruang Rawat Inap Anak - Emir Fajar Hizrian; Dewi Kusumaningsih; Aryanti Wardiyah (Jurnal Kreativitas Pengabdian Kepada Masyarakat (PKM), 2026)
ABSTRACT According to the World Health Organization (WHO), nosocomial infections cause 1.4 million deaths per day worldwide. In Indonesia, nosocomial infections prolong hospital stay for 5-30 days with a mortality rate of 23.6%. This study aims to optimize nursing supervision for the implementation of universal precautions (Hand Wash) which is carried out in the pediatric inpatient room at Pertamina Bintang Amin Hospital Bandar Lampung in 2023. This type of descriptive research uses a case study approach. Subjects in the reports of the head of the nursing field, the head of the children's room, the team leader and the implementing nurse in the Children's Room of the Pertamina Bintang Amin Hospital Bandar Lampung were 12 people. the supervision carried out has an influence on the performance of nurses in carrying out hand washing. The results of the observation revealed that after supervision in carrying out hand washing was carried out properly, the implementation of hand washing was carried out thoroughly. Strength: nurses in the pediatric room understand supervision. Weakness: Implementation of unscheduled nursing supervision. Nurses have never received Training on Supervision. There is no guide format for the implementation of nursing supervision in the room. Opportunity There is good cooperation between health education institutions and hospitals in student clinical practice activities. The existence of hospital policies provides opportunities for nurses to improve education. Threat There are high demands from patients and their families to get professional nursing services. Efforts to optimize nursing supervision in pediatric inpatient rooms by optimizing the planning function of the head of the room, such as making guidelines, SOPs and evaluating supervision programs. Keywords: Optimization, Nursing Supervision.  ABSTRAK Menurut World Health Organisation (WHO), infeksi nosokomial menyebabkan 1,4 juta kematian perhari di seluruh dunia. Di Indonesia, infeksi nosokomial memperpanjang keperawatan di rumah sakit selama 5-30 hari dengan tingkat kematian 23,6%. Penelitian ini bertujuan melakukan optimalisasi supervisi keperawatan pelaksanaan universal precaution (Hand Wash) yang dilakukan di ruang rawat inap anak RS Pertamina Bintang Amin Bandar Lampung Tahun 2023. Jenis penelitian deskriptif dengan menggunakan metode pendekatan studi kasus. Subjek pada laporan kepala bidang keperawatan, kepala ruangan anak, ketua tim dan perawat pelaksana di Ruang anak Rumah Sakit Pertamina Bintang Amin Bandar Lampung sebanyak 12 orang. supervisi yang dilakukan mempunyai pengaruh dengan kinerja perawat dalam pelaksanaan cuci tangan. Hasil pengamatan diketahui bahwa setelah dilakukan supervisi dalam melakukan cuci tangan dilaksanakan dengan baik, pelaksanan cuci tangan dilakukan secara menyeluruh. Strenght : perawat di ruang anak  telah mengerti tentang supervisi. Weakness: Pelaksanaan supervisi keperawatan tidak terjadwal. Perawat belum pernah mendapatkan Pelatihan tentang Supervisi. Belum terdapat format panduan pelaksanaan Supervisi keperawatan di ruangan. Opportunity Adanya kerja sama yang baik antara institusi pendidikan kesehatan dan rumah sakit dalam kegiatan praktek klinik mahasiswa. Adanya kebijakan rumah sakit memberikan kesempatan bagi perawat untuk meningkatkan pendidikan. Threat Adanya tuntutan tinggi dari pasien dan keluarga pasien untuk mendapatkan pelayanan keperawatan professional. Upaya optimalisasi supervisi keperawatan diruang rawat inap anak dengan melakukan optimalisasi fungsi perencanaan kepala ruangan, seperti pembuatan panduan, SOP dan penilaian program supervisi. Kata Kunci: Optimalisasi, Supervisi Keperawatan.